The Australian ready-to-drink beverages tax missed its target age group - Alexeev, Sergey; Weatherburn, Donald (My University, 2021)
During 2008 and 2009, the Australian Government increased the tax on ready-to-drink alcoholic beverages by 70% to discourage drinking among adolescents. To evaluate the tax, we use the difference-in-difference and comparative interrupted time series estimators, where age is used to define the control and treatment groups. This methodology is applied to the Household Income and Labour Dynamics in Australia survey. We show that the tax did not affect the alcohol consumption of those aged under 25 (the tax targeted age group) but substantially reduced drinking among those aged 25-69, reducing their average daily consumption of standard drinks by 8.9% from 2010 to 2018. The age group under 25 did not respond to the tax likely because of product substitution. Alcohol price policy may need to acknowledge complex substitute/complement relationships between beverages and consider a floor price on alcohol or a uniform volumetric tax per standard drink.
International Journal of Drug Policy
Keywords: Alcopops; Australia; Drinking; Ready-to-drink beverages; Adolescents and youth; Ageing; Government, law and policy; Health and wellbeing; Lifestyle; Surveys and survey methodology